Preliminary results of studies on the distribution of invasive alien vascular plant species occurring in semi-natural and natural habitats in NW Poland - Popiela, Agnieszka; Łysko, Andrzej; Sotek, Zofia; Ziarnek, Krzysztof (Biodiversity: Research and Conservation, 2015)
In Western Pomerania, as in other areas of Europe, alien species play an increasingly important role. In particular, invasive plants tend to spread rapidly and in large numbers which may reduce diversity of native species, leading to the phenomenon of “trivialisation of flora”, and transform ecosystems. The list of invasive species (32 taxa) includes alien species occurring throughout Western Pomerania, and penetrating natural or semi-natural habitats. The second group consists of potentially invasive species (23 taxa), i.e. those distributed across the area under study and tending to increase the number of their localities in semi-natural and natural habitats, taxa invasive only locally, as well as species with missing data, which does not currently allow including them into the first group. Invasive weeds, as well as some epecophytes and archaeophytes occurring only on anthropogenic sites and tending to spread, were not taken into account. Among hemiagriophytes, the most common and troublesome ones are: Conyza canadensis, Erigeron annuus, Lolium multiflorum, Lupinus polyphyllus, Solidago canadensis, S. gigantea. Among holoagriophytes, i.e. the taxa which received the highest naturalisation status, very expansive species, successful in land colonisation, like Acer negundo, Bidens frondosa, B. connata, Clematis vitalba, Elodea canadensis, Epilobium ciliatum, Heracleum sosnowskyi, Impatiens glandulifera, I. parviflora, Padus serotina, Quercus rubra and Robinia pseudoacacia, should be given particular attention. Among the invasive and potentially invasive species, most taxa penetrate plant communities of the Artemisietea and Molinio-Arrhenatheretea class, followed by Querco-Fagetea, Vaccinio-Piceetea, Stellarietea mediae, Salicetea purpurae and Koelerio-Corynophoretea. The number of invasive species is twice as high when compared to the situation of these species in Poland; on the contrary, the number of species inhabiting anthropogenic, semi-natural and natural habitats is two times lower, while that of holoagriophytes and hemiagriophytes is 56.3% and 43.7%, respectively. It seems that in the case of some invasive and potentially invasive species, a decrease in the number of their locations may be observed from the west to the east (e.g. for Acer negundo, Bromus carinatus, Clematis vitalba, Helianthus tuberosus, Lycium barbarum, Reynoutria japonica, Rosa rugosa, Vicia grandiflora). Distribution patterns for some species (e.g. for Parthenocytisus inserta or Xanthium albinum) are indicative of a likely major role of the Odra River valley in the spreading of invasive species. It should be kept in mind that the area of the North-West Poland is poorly examined in terms of its flora, so the results provided in this paper are tentative. Nevertheless, the maps illustrate colonisation trends and directions and, moreover, have been so far the only attempt to synthesise this problem in NW Poland.